Self-determination and relationship quality in consensually non-monogamous individuals - Portillo, Maria Fernanda (Kansas State University, 2024)
Research on Consensual Non-Monogamy (CNM) typically compares diverse relationship structures to monogamy, further perpetuating the societal belief that monogamy should be the standard for relationships, which is known as mononormativity (Moors, et al., 2019). Guided by Self-Determination Theory, this study aimed to determine how motives for being in a CNM relationship, internalized CNM negativity, and discrimination were associated with relationship quality. A latent variable structural equation model was used to test these associations. Higher levels of self-determined reasons for being in a CNM relationship were associated with higher levels of relationship quality (b = 2.54, p = .007, β = .22). Higher levels of internalized CNM negativity (b = -1.75, p = .043, β = -.15), discrimination (b = -.36, p = - .014, β = -.16), and neuroticism (b = -1.75, p = .027, β = -.14) were associated with lower levels of relationship quality. Relationship structure (i.e., poly, swinging, open), relationship length, and relationship status were not significantly related to relationship quality. These findings highlight that having self-determined reasons for engaging in a CNM relationship are important for relationship quality and that a person’s sociocultural context may have a negative impact on optimal relationship functioning. Therapists working with CNM individuals must address their biases towards diverse relationship structures in order to help clients effectively deconstruct harmful mononormative beliefs. Additionally, addressing these constructs in relationship therapy can provide a beneficial start to treatment, as our cultural context heavily influences how we interact with ourselves and others relationally.
Keywords: Consensual non-monogamy; Discrimination; Internalized CNM negativity; Relationship quality; Self-determination theory